2023
DOI: 10.1007/s00289-023-04765-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a chitosan derivative bearing the thiadiazole moiety and evaluation of its antifungal and larvicidal efficacy

Abstract: A new chitosan derivative bearing a new thiadiazole compound was developed, and its antifungal and larvicidal activities were investigated. The chitosan derivative (coded here as PTDz-Cs) was synthesized by the reaction between the carboxylic derivative of the thiadiazole moiety and chitosan. Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (1H/13C-NMR), gas chromatography–mass spectrometry (GC–MS), elemental analysis, X-Ray diffraction (XRD), thermogravimetric analysis (TGA), and X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Mohamed et al developed a novel 1,3,4-thiadiazole-modified chitosan, which exhibited excellent antibacterial activity against Escherichia coli , Staphylococcus aureus , Bacillus subtilis , Pseudomonas aeruginosa , and Candida albicans [ 67 ]. Another study found that thiadiazole-modified chitosan possessed higher fungal inhibitory activity and the ability to kill early larvae compared to chitosan [ 68 ]. Chitosan can be chemically modified by clicking chemistry.…”
Section: Chitosan and Chitosan Modificationmentioning
confidence: 99%
“…Mohamed et al developed a novel 1,3,4-thiadiazole-modified chitosan, which exhibited excellent antibacterial activity against Escherichia coli , Staphylococcus aureus , Bacillus subtilis , Pseudomonas aeruginosa , and Candida albicans [ 67 ]. Another study found that thiadiazole-modified chitosan possessed higher fungal inhibitory activity and the ability to kill early larvae compared to chitosan [ 68 ]. Chitosan can be chemically modified by clicking chemistry.…”
Section: Chitosan and Chitosan Modificationmentioning
confidence: 99%
“…The acylation reaction has the potential to disrupt both the intramolecular and intermolecular H-bonding within the CS, leading to a reduction in its crystallinity and enhancing water solubility [68]. In recent studies, researchers have explored the reaction of CS with pre-prepared acyl chlorides or acetic acid containing diverse heterocycles like benzothiazole, thiadiazole, thymine, or pyrazoles to produce the acylated CS bearing the heterocycles (2d, 2e) [69][70][71][72][73][74][75][76]. Similarly, Zhang's group developed CS-bearing quinolinyl urea derivatives (2f).…”
Section: Alkylation Acylation and Schiff Base-based Chitosan Derivativesmentioning
confidence: 99%
“…Introduction of heterocyclic compounds into the structure of quaternized chitosan can increase the antimicrobial activity of the compound. Previous chemical modifications of chitosan with heterocycles have shown promising biological activities [ 10 , 11 , 12 , 13 ]. In a number of works, the use of chitosan derivatives, including imidazole derivatives, has been shown in the development of hemocompatible delivery systems for medicinal products or to achieve the thromboresistance of surfaces of medical devices/materials (nanoparticles, frameworks, hydrogels and membranes) in contact with blood [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%